2015
DOI: 10.1099/jmm.0.000082
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of clotrimazole against Candida albicans depends on carbon sources, growth phase and morphology

Abstract: Vulvovaginal candidiasis, a superficial infection caused predominantly by the pathogenic fungus Candida albicans, is frequently treated with clotrimazole. Some drug formulations contain lactate for improved solubility. Lactate may modify C. albicans physiology and drug sensitivity by serving as a carbon source for the fungus and/or affecting local pH. Here, we explored the effects of lactate, in combination with pH changes, on C. albicans proliferation, morphology and clotrimazole sensitivity. Moreover, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…This included filastatin [66], ascorbic acid [66], mucins [67], gymnemic acids [68], and quinacrine [69] to name only a few. Of note, even known antifungals seem to have specific effects on the different morphological forms of C. albicans, and one azole was shown to force the fungus into the yeast growth mode, potentially due to reduced ergosterol content of the cell membrane [70]. In agreement with that information, one study identified ergosterol synthesis as a critical aspect in a large-scale functional screening to identify regulators of morphogenesis [7].…”
supporting
confidence: 59%
“…This included filastatin [66], ascorbic acid [66], mucins [67], gymnemic acids [68], and quinacrine [69] to name only a few. Of note, even known antifungals seem to have specific effects on the different morphological forms of C. albicans, and one azole was shown to force the fungus into the yeast growth mode, potentially due to reduced ergosterol content of the cell membrane [70]. In agreement with that information, one study identified ergosterol synthesis as a critical aspect in a large-scale functional screening to identify regulators of morphogenesis [7].…”
supporting
confidence: 59%
“…Biofilm MIC 80 was determined as the lowest concentration that inhibited ≥80% of fungal biofilm growth. RPMI-1640 of pH 7.2 and pH 4.0 were used as growth medium, respectively, to examine the effect of different environmental acidity on antifungal efficacy as local pH has been found to impact on the antifungal-mediated killing of C. albicans (Ilkit and Guzel, 2011;Kasper et al, 2015).…”
Section: Antifungal Susceptibility Tests For Planktonic Cells and Abimentioning
confidence: 99%
“…Moreover, antimicrobial activity can be microorganism- and/or morphology-dependent. Kasper et al (2015) compared the clotrimazole antifungal action against C. albicans morphotypes and showed that hyphae were much more sensitive to this azole than the yeast form. In fact, studies have showed that fungal morphological changes are usually associated with intense modification of cell surface, physiology and immunology ( Klein and Tebbets, 2007 ; Erwig and Gow, 2016 ).…”
Section: Resultsmentioning
confidence: 99%